Hubungan antara Efikasi Diri dengan Pengambilan Keputusan Karir Siswa - Warohma, Chika Febtri; Sucipto, Sigit Dwi (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2023)
Self-efficacy is very important for students in the process of making career decisions. Students who have high self-efficacy will be confident in their ability to make career choices for their future. This study aims to determine the relationship between self-efficacy andcareer decision making in class XI students of SMA Negeri 7 Prabumulih. This research is a quantitative study using the correlation method with a sample of 74 students from 297 populations taken using a proportional random sampling technique. The research instrument used a self-efficacy scale of 24 items and career decision making of 27 items in the form of a Likert scale obtained through the distribution of instruments. Data analysis in this study uses pearson product moment correlation. The results of data analysis show that class XI students of SMA Negeri 7 Prabumulih have self-efficacy and career decision making in the medium category with a correlation coefficient (rxy) of 0.247 as rcount and rtable of 0.228 from 74 respondents with a significance level of 5% so that the hypothesis test is rcount > rtable then Ho is rejected and Ha is accepted. Thus it can be concluded that there is a positive relationship between self-efficacy and career decision making in class XI students of SMA Negeri 7 Prabumulih.